Յոթնագրյանքների առեղծվածը - Վաչագան Միրզոյան (ՀՀ ԳԱԱ հրատ.)
Открыты некоторые тайны армянского маштоцкого алфавита и установлено, что структура алфавита вытекает из математических закономерностей. Расшифрован текст семизаписи рукописи № 1711 и обосновано, что армяне производили суммирование чисел с помощью пальцев руки, а для умножения считали необходимым и достаточным знание таблицы умножения от 1-го до 5-ти и умножение цифры на 10n, а дальнейшее суммирование выполняли также посредством пальцев руки. Some secrets of the Armenian alphabet created by Mashtots have been discovered and it has been proved that the structure of the alphabet results from mathematical regularities known to Armenians. The text of the yotnagir manuscript № 1711 has been decoded and it has been substantiated that the Armenians summed up numbers with the help of fingers and that they considered necessary and sufficient knowledge of multiplication table from 1 to 5 and knowledge of multiplying numbers by 10n and further summarizing was again done with the help of fingers.
Keywords: History; Philology; Linguistics; Language and Literature; D History